The Relationship between Knowledge of Menstruation and Anxiety Levels in Facing Menstruation among Elementary School Students - Andra Netta Feriskyaningrum Arissandi; Nining Febriyana; Endyka Erye Frety (Journal La Medihealtico, 2026)
Menstruation is a normal biological process; however, for elementary school students with limited knowledge, it may provoke fear and anxiety. Previous studies indicate that 54.1% of young girls possess low levels of knowledge about menstruation, which contributes to heightened anxiety during menarche. Adequate knowledge is considered crucial for improving mental readiness. This study emphasizes the role of knowledge in comparison with other influencing factors, highlighting the importance of menstrual education in shaping students’ understanding. This quantitative study employed a cross-sectional design. The sample comprised 115 female students in grades 4, 5, and 6 from SDN Kaliasin 1, Kaliasin 5, and Kaliasin 7 in Surabaya who had not yet experienced menarche. Data were collected using questionnaires to assess knowledge of menstruation (independent variable) and anxiety levels (dependent variable), measured with the Zung Self-Rating Anxiety Scale (Z-SAS). Data analysis was conducted using the Spearman Rank correlation test. The findings showed that 81.0% of respondents had a moderate level of knowledge regarding menstruation, while 12.4% had low levels of knowledge. In terms of anxiety, 55.7% of students experienced moderate anxiety when facing menarche. The Spearman Rank test yielded a p-value of 0.005 with a low correlation coefficient (r = 0.296), indicating a statistically significant relationship between menstrual knowledge and anxiety levels. There is a significant relationship between knowledge of menstruation and anxiety levels among elementary school students. Comprehensive menstrual education is essential to enhance students’ mental preparedness and to reduce anxiety when facing menarche.